Analysis of predictability of F‐18 fluorodeoxyglucose‐PET/CT in the recurrence of papillary thyroid carcinoma. (19th August 2016) - Kim, Suk Kyeong; So, Young; Chung, Hyun Woo; Yoo, Young Bum; Park, Kyung Sik; Hwang, Tae Sook; Kim, Bokyung; Lee, Won Woo
Abstract: Whether preoperative F‐18 fluorodeoxyglucose (FDG)‐positron emission tomography/computed tomography (PET/CT) can predict recurrence of papillary thyroid carcinoma (PTC) remains unclear. Herein, we evaluated the potential of primary tumor FDG avidity for the prediction of tumor recurrence in PTC patients. A total of 412 PTC patients (72 males, 340 females; age: 47.2 ± 12.2 years; range: 17–84 years) who underwent FDG‐PET/CT prior to total thyroidectomy ( n  = 350), subtotal thyroidectomy ( n  = 2), or lobectomy ( n  = 60) from 2007 to 2011 were analyzed. The predictive ability for recurrence was investigated among various clinicopathological factors, BRAF V 600E mutation, and preoperative FDG avidity of the primary tumor using Kaplan–Meier (univariate) and Cox proportional hazards regression (multivariate) analyses. Of the 412 patients, 19 (4.6%) experienced recurrence, which was confirmed either by pathology ( n  = 17) or high serum thyroglobulin level ( n  = 2), during a mean follow‐up period of 43.9 ± 16.6 months. Of the 412 patients, 237 (57.5%) had FDG‐avid tumors (maximum standardized uptake value, 7.1 ± 7.0; range: 1.6–50.5). Kaplan–Meier analysis revealed that tumor size ( P  = 0.0054), FDG avidity of the tumor ( P  = 0.0049), extrathyroidal extension ( P  = 0.0212), and lymph node (LN) stage ( P  < 0.0001) were significant predictors for recurrence. However, only LN stage remained a significant predictor in the multivariate analysis ( P  < 0.0001). Patients with FDG‐avid tumors had higher LN stage ( P  < 0.0001), larger tumor size ( P  < 0.0001), and more frequent extrathyroidal extension ( P  < 0.0001). In conclusion, FDG avidity of the primary tumor in preoperative FDG‐PET/CT could not predict the recurrence of PTC. LN stage was the only identified predictor of PTC recurrence. Abstract : FDG (fluorodeoxyglucose)‐avid papillary thyroid carcinomas showed worse pathological prognostic factors. Lymph node metastasis was the only predictor of papillary thyroid carcinoma (PTC) recurrence. Preoperative FDG‐PET/CT may play a potential role for the prediction of papillary thyroid carcinoma recurrence.